Pengaruh Intervensi Senam Hamil dalam Menurunkan Stres dan Meningkatkan Kualitas Tidur Ibu Hamil Trimester III: The Effect of Pregnancy Exercise Intervention in Reducing Stress and Improving Sleep Quality on Pregnant Women in Their Third Trimester - Witari, Ni Nyoman Deni (Stikes Wira Medika Bali, 2020)
Pregnancy exercise is one of the sports used for preparing pregnant women mentally and physically in facing their pregnancy. Problems that often arise during pregnancy are poor sleep quality, high maternal stress level, lower back pain, increased urination frequency and leg cramps. The purpose of this study is to determine the effect of pregnancy exercise on stress and sleep quality as well as the correlation between them. This study is an analytical study with one group pretest-posttest design with a sample of 50 people using a purposive sampling technique based on inclusion and exclusion criteria. The data collection was done through a primary data collection by filling in the Depression Anxiety and Stress Scale (DASS) questionnaire and The Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data was then processed using the Wilcoxon test to see differences in stress levels and sleep quality before and after the implementation of pregnancy exercise on pregnant women and the Spearman test to see the correlation between stress level and sleep quality of pregnant women. The results of stress level before and after the implementation of pregnancy exercise (p = 0.000) and the quality of sleep before and after pregnancy exercise (p = 0.000) were both statistically significant. The results also showed that there was no correlation between stress level and sleep quality of pregnant women (p = 0.088).